Parâmetros oftálmicos em diferentes espécies de cervídeos brasileiros mantidos em cativeiro - Crivelaro, Roberta Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Brazilian deer, some of which are at risk of extinction, are not free from ophthlamic lesions. Knowledge about ophthalmic parameters is particularly important, especially for diagnostics and therapeutics of ophthalmopaties that can affect them. At this study, tear production, measured with Schirmer tear test, introcular pressure, measured with applanation tonometry, ocular biometry, measured from ultrasonographic images, head biometry, using a caliper rule, and retina conditions, by electroretinography, were evaluated. Several adult captive deer, from eight different species (Mazama americana, Mazama nemorivaga, Mazama gouazoubira, Mazama nana, Mazama bororo, Blastocerus dichotomus, Odocoileus virginianus e Ozotoceros bezoarticus), free from ophthalmic lesions, were studied and compared. Tear production did not differ between studied species and were lower than values in domestic and other wild animals. Intraocular pressure were similar to other animal from resembling families. IOP data showed differences between species, where the highest values were found in O. bezoarticus (19 mmHg), and the lowest in M. nemorivaga (5 mmHg). Corneal thickness was higher in animals living in areas with dense vegetation, while lower values were found in animals who live in areas with open vegetation. The same correlation could me made when looking at lens thickness and axial lenght, where species with bigger eyes live in areas with dense vegetation, while species with smaller eyes live in areas with open vegatation. Electroretinography did not show differences between species

Cervídeos da fauna brasileira, muitos dos quais sob risco de extinção, não estão livres de afecções oculares. O conhecimento sobre os parâmetros oftálmicos é particularmente importante, notadamente para o diagnóstico e a terapêutica das oftalmopatias que os acometem. Foram avaliadas a produção lacrimal, empregando-se o teste da lágrima de Schirmer; a pressão intraocular, pela tonometria digital de aplanação; a biometria ocular, à ultrassonografia; a biometria craniana, à paquimetria; e as condições da retina, pela eletrorretinografia. Estudaram-se e compararam-se as espécies Mazama americana, Mazama nemorivaga, Mazama gouazoubira, Mazama nana, Mazama bororo, Blastocerus dichotomus, Odocoileus virginianus e Ozotoceros bezoarticus, livres de afecções oftálmicas. Valores de Schirmer mostraram-se menores que os referidos para animais domésticos e selvagens e não diferiram entre as espécies avaliadas. Valores de pressão intraocular não diferiram das de animais de famílias semelhantes já estudadas. Diferenças entre as espécies foram encontradas relativamente à PIO, estando o maior valor com o O. bezoarticus (19 mmHg) e o menor com o M. nemorivaga (5 mmHg). Animais que habitam áreas de vegetação predominantemente densa exibiram córneas mais espessas. Animais que habitam áreas de vegetação predominantemente aberta, exibiram córneas mais delgadas. Relativamente à espessura da lente e ao comprimento axial do olho, espécies com olhos de maior tamanho foram as de áreas de vegetação fechada e espécies com olhos de menor tamanho corresponderam às de vegetação aberta. A eletrorretinografia não apontou diferenças entre as espécies
Keywords: Cervídeo; Oftalmologia veterinaria; Olhos - Exame; Valores de referencia (Medicina); Biometria; Veterinary ophthalmology